Romaine—Lactuca sativa L. - James M. Stephens (EDIS)
This document describes romaine lettuce (Lactuca sativa L.), highlighting its historical origins, physical characteristics, and cultivation practices in Florida. It outlines suitable growing seasons, recommended varieties, planting techniques, and maintenance tips for successful growth. The document also addresses pest management, harvesting methods, and storage considerations, emphasizing romaine’s popularity as a crisp, nutritious salad green. Original publication date May 1994.